Chasing two hares with two hounds: a strategy for maintaining core functions of an acute care hospital amid COVID-19 crisis - Lee, Wang Jun (Taehan Ŭisa Hyŏphoe chi, 2021)
Amid the coronavirus disease 2019 (COVID-19) crisis, the core functions of an acute care hospital are to continuously provide essential clinical care services to patients from community at large. The dual track healthcare system (DTHS) is a strategy for preventing the hospital infection and allocating the resources of an acute care hospital to treat COVID-19 patients while simultaneously providing indispensable clinical care services for non-COVID-19 patients. The key elements of DTHS include compartmentalizing the space within independent buildings, allocating buffer zones for patients who have not been confirmed for COVID-19 infection but require inpatient treatment, delegating manpower with appropriate support, establishing competent in-house laboratory that enables universal COVID-19 screening via reverse transcriptase polymerase chain reaction and employing real-time communication technology. The effectiveness of DTHS was confirmed through the results of questionnaire surveys of hospital patients and the research on the qualitative and quantitative changes in the provision of fundamental care services including both acute and continuous clinical care after the care for COVID-19 patients in the hospital. With a potential for subsequent explosive community infections, the pandemic public health crisis rendered by COVID-19 will be prolonged. Therefore, each acute care hospital should prepare its measures and strategies to mimic the DTHS for the maintenance of the hospital’s core functions in anticipation of a revisit of the situation